THE IMPLEMENTATION OF PROCESS APPROACH COMBINED WITH SCREENCAST-O-MATIC AND BOOKCREATOR TO IMPROVE STUDENTS’ ARGUMENTATIVE WRITING - Anak Agung Putri Maharani; Made Hery Santosa (LLT Journal: A Journal on Language and Language Teaching, 2021)
Within the 21st century learning framework, pupils are demanded to argue more reasonably over massive information that they receive. This study was conducted due to the imperative function of argumentative writing skill within this century by utilizing innovative argumentative writing approaches combined with screencasting and bookcreating projects. Involving 31 sophomores in English Language Education Study Program, a descriptive qualitative research design was utilized. Their progress in argumentative writing classroom and views were gauged to reach the conclusion. Threefold methods of collecting data were administered; observation, interview, and questionnaire. The collected data from, afterwards, were filtered, presented, analysed and verified. It was found that the use of process approach combined with Screencast-o-matic and Bookcreator had crucial contribution in argumentative writing development. The participants responded positively towards the implementation of process approach combined with Screencast-o-matic and Bookcreator.